2013
DOI: 10.1002/pmic.201200386
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomics study of early biofilm formation process ofAcidithiobacillus ferrooxidansATCC 23270 on pyrite

Abstract: Acidithiobacillus ferrooxidans is a chemolithoautotrophic, mesophilic Gram-negative bacterium able to oxidize ferrous iron, sulfur, and metal sulfides. It forms monolayer biofilms where extracellular polymeric substances are essential for cell attachment and metal sulfide leaching. High-throughput proteomics has been applied to study the early process of biofilm formation on pyrite by At. ferrooxidans ATCC 23270. After 24 h contact with the mineral, planktonic and sessile (biofilm) cell subpopulations were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 86 publications
0
52
0
Order By: Relevance
“…In addition, a putative nucleotide-diphosphate reductase protein (NrdA) (AFE_2638) was overexpressed in A. ferrooxidans cells grown in sulfur in the presence of copper (Table 2). Very recently, an increased level of (NrdA) (AFE_2638) was reported in biofilms of A. ferrooxidans ATCC 23270 grown in pyrite [57]. On the other hand, this protein did not change its levels in the presence of copper in ferrous iron-grown cells (Table 5).…”
Section: Cell Motility and Secretionmentioning
confidence: 93%
“…In addition, a putative nucleotide-diphosphate reductase protein (NrdA) (AFE_2638) was overexpressed in A. ferrooxidans cells grown in sulfur in the presence of copper (Table 2). Very recently, an increased level of (NrdA) (AFE_2638) was reported in biofilms of A. ferrooxidans ATCC 23270 grown in pyrite [57]. On the other hand, this protein did not change its levels in the presence of copper in ferrous iron-grown cells (Table 5).…”
Section: Cell Motility and Secretionmentioning
confidence: 93%
“…These changes may be related to a glutathione-driven response against an increased exposure of cells to ROS after 24 h contact with pyrite. Also, in the PP, a thiol-dependent peroxidase (OsmC/Ohr family), probably involved in defense against oxidative stress caused by exposure to organic hydroperoxides, was found increased (Vera et al 2013a). In addition, A. ferrooxidans T GR gene expression was previously found to be induced after bacterial exposure to copper, suggesting its involvement in recovering GSH pools and cell homeostasis (Xia et al 2011).…”
Section: Enhanced Resistance Of Pyrite-grown Cells Against Presence Omentioning
confidence: 95%
“…By high-throughput proteomics, it was shown that A. ferrooxidans T undergoes several metabolic adaptations after 24 h of biofilm formation on pyrite. Functions such as EPS synthesis and biosynthesis of electron-carriercontaining molecules as well as osmotic and oxidative stress responses were enhanced in biofilm cells (Vera et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Early biofilm formation involves capsular polysaccharide production (CPS), up-regulation of genes related to pili and EPS production, motility and quorum sensing, synthesis of cell wall structures, specific proteases, stress response chaperons, and mixed acid fermentation [316][317][318][319]. Proteomic analysis revealed similar results with the addition of increased production of osmolarity sensing, outer-membrane efflux, iron uptake, sulfate uptake and assimilation, glutathione/coenzyme/cofactor biosynthesis, lipoproteins, and nucleotidases [320].…”
Section: Attachment Of Extreme Thermoacidophiles To Surfacesmentioning
confidence: 96%